Bioremediation of Diesel Oil Spill by Filamentous Fungus Trichoderma reesei H002 in Aquatic Environment - Nazifa, Tasnia Hassan; Ahmad, Mohd Azlan; Hadibarata, Tony; Aris, Azmi (International Journal of Integrated Engineering, 2019)
Bioremediation of aquatic environment could be a response to the oil spills threats. In this paper, Trichoderma reesei H002, a filamentous ascomycete fungus isolated from a polluted site in an orchard garden, Johor, Malaysia, was experimented for its biodegradation ability to degrade diesel oil. Varying nitrogen and carbon sources, pH, agitation on diesel oil by Trichoderma reesei H002 in liquid media were examined to find their impacts on TPHs, alkane, aromatic and NSO fractions of diesel oil degradation. Glucose and yeast extract were the most suitable nutrients for the development of T. reesei H002 and increased the degradation of total petroleum hydrocarbons (TPHs up to 94.78% at the end of the study (40 days) at 25 0C. The degradation of TPHs were performed by gravimetric analysis and degradation of alkane and aromatic fractions were confirmed by GC-FID analysis. Based on the findings of T. reesei H002 for the biodegradation of diesel oil, it can be proposed that T. reesei H002 can be applied to bioremediate diesel oil spill in aquatic environment, therefore protect the ecosystem.